Complex Words, Causatives, Verbal Periphrases and the Gerund: Romance Languages versus Czech (A Parallel Corpus-Based Study) - Olga Nádvorníková (Karolinum Press, 2020)
The monograph focuses on the typological differences between the four most widely spoken Romance languages (Spanish, Portuguese, French and Italian) and Czech. Utilizing data from InterCorp, the parallel corpus project of the Czech National Corpus, the book analyses various categories (expression of potential non-volitional participation, iterativity, causation, beginning of an action and adverbial subordination) to discover differences and similarities between Czech and the Romance languages. Due to the massive amount of data mined, as well as the high number of languages examined, the monograph presents general and individual typological features of the four Romance languages and Czech that often exceed what has previously been accepted in the field of comparative linguistics.